Characterization of the cyanobacterium Oscillatoria sp. isolated from extreme sulphureous water from Los Baños de la Hedionda (S Spain) - Martín-Clemente, Elena; Melero-Jiménez, Ignacio José; Reul, Andreas; Hernández-López, Miguel; Salvo-Tierra, Ángel Enrique; Bañares-España, Elena; García-Sánchez, María Jesús; Flores-Moya, Antonio; Melero-Jiménez, Ignacio José (My University, 2017)
Los Baños de la Hedionda (Málaga, S Spain) is a natural sulphureous spa (150-200 µM sulphide). Although this high sulphide levels can affect the photosynthetic process, there are numerous photosynthetic microorganisms inhabiting the spa. Among them, we isolated a strain of the cyanobacterium Oscillatoria sp., a genus well known by its tolerance to sulphide. Objectives Firstly, to analyze the photosynthetic characteristics and growth rate of the isolated strain, as well as the effect of the presence of sulphide in both processes. Secondly, to determine the limit of genetic adaptation of this strain to sulphide. Methods The resistance of the isolated strain to sulphide was studied by analyzing the effect of increasing sulphide levels (up to 1600 µM) on photosynthetic performance and growth. The limit of genetic adaptation was explored using an evolutionary experimental design named as ratchet protocol. This design allows discerning the maximum capacity of genetic adaptation of Oscillatoria sp. to the exposure of increasing doses of sulphide Conclusions The strain showed maximum growth rates at 200 µM sulphide although reduced rates can be found up to 800 µM sulphide. A significant increase in resistance was achieved in all derived populations during the ratchet experiment (surviving at sulphide concentrations higher than 2 mM). Moreover, they showed different evolutionary potential to adapt to sulphide, depending on historical contingency.
Keywords: Cianobacterias; Oscillatoria sp.; Sulphide; Ratchet protocol; Adaptation